George Washington - Kallen, Stuart A., 1955- (Minneapolis, MN. : ABDO Pub., 2001)
Presents a biography of the Commander in Chief of the Continental Army and first president of the United States.
"Where on the Web?"--p. 61.
Includes index.
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography -- Juvenile literature; Presidents